2018
DOI: 10.1142/s0219455418500256
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Review on Modal Identification and Damage Detection of Bridges by Moving Test Vehicles

Abstract: In 2004, Yang and co-workers proposed the extraction of bridge frequencies from the dynamic response of a moving test vehicle [Y. B. Yang, C. W. Lin and J. D. Yau, Extracting bridge frequencies from the dynamic response of a passing vehicle, J. Sound Vib. 272 (2004) 471–493] and verified the technique by a field test [C. W. Lin and Y. B. Yang, Use of a passing vehicle to scan the bridge frequencies — An experimental verification, Eng. Struct. 27(13) (2005) 1865–1878]. This technique was extended to constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(104 citation statements)
references
References 89 publications
1
81
0
3
Order By: Relevance
“…Several researchers have shown the importance of the vehicle velocity for the successful identification of bridge natural frequencies from indirect measurements [4,10]. In this section, the same simulation is repeated with lower vehicle velocities to find if the EMD method can perform well in lower speeds.…”
Section: Effect Of Vehicle Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have shown the importance of the vehicle velocity for the successful identification of bridge natural frequencies from indirect measurements [4,10]. In this section, the same simulation is repeated with lower vehicle velocities to find if the EMD method can perform well in lower speeds.…”
Section: Effect Of Vehicle Velocitymentioning
confidence: 99%
“…Over the past decade, many researchers have been developing indirect bridge monitoring methods. A comprehensive review of the most recent methods proposed for indirect bridge monitoring can be found in the works of Malekjafarian et al [3] and Yang and Yang [4]. Figure 1 shows an overview of the state-of-the-art in this field.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the results of identifications of structural damages using modal frequencies to assess the overall damages of structures and study the overall damage information of the structures have shown high antinoise and identification accuracy abilities. Also, these types of methods have been observed to have convenient measurement adaptabilities [29][30][31]. Furthermore, this method has been widely used in aviation, aerospace, precision machine tools, and other fields in developed countries, for fault diagnosis, load identification, and dynamic modification.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, structural health monitoring (SHM) can be considered as an efficient tool to monitor the structural safety based on global or local response . Additionally, regular monitoring of modal properties can provide useful data, for example, loss of stiffness, natural frequency shift, breakage in connections, or deterioration of materials …”
Section: Introductionmentioning
confidence: 99%